ANALISIS SOAR: KERANGKA BERPIKIR POSITIF UNTUK MENGHADAPI TANTANGAN DAN PELUANG PENDIDIKAN ADMINISTRASI PERKANTORAN DI ERA REVOLUSI INDUSTRI 4.0 - Choirul Anam (Program Studi Pendidikan Ekonomi Universitas Riau, 2020)
Industrial Revolution 4.0 has become a phenomenon that is able to change variousaspects of life including the field of education, especially vocational education. Thepresence of information digitalization and industrial automation has led to severalfields of study deemed irrelevant to today's needs, one of which is officeadministration. Based on these conditions it is known that office administrationeducation faces new challenges and opportunities in order to survive. During thistime some parties view that this field of study cannot survive with the presence ofvarious applications that replace the role of skilled workers. This anxiety grew whenthe government decided to conduct a moratorium on admission of new studentsmajoring in office administration. However, on the other hand there is a fact that thenumber of interested in the Department of Office Administration Education in tertiaryinstitutions remains in a high position. Therefore, this article tries to look at it fromanother perspective regarding the opportunities and challenges of officeadministration education in the Industrial Revolution 4.0 era by putting forward apositive attitude through SOAR analysis. The results of this discussion recommendthat office administration education focus on the opportunities and strengths that arethen adapted to the needs of the workforce and the industrial world.